Optimization of CuInSSe-Based Solar Cell Simulated by SCAPS-1D Software: Role of 30% Efficiency - Abdulameer, Ameer F.; Kadem, Burak Yahya; Alfahed, R.K. Fakher; Al Hashimi, Mohammed K. (Iraqi Journal of Science, 2026)
Copper Indium Sulfur-Selenide (CISSe)-based solar cell is examined by optimization several aspects including absorber layer thickness, buffer layer thickness, window layer thickness, working temperatures and energy band gap values. The optimization of these factors has resulted in optimum absorber layer thickness of 3000 nm, optimum CdS thickness of 10 nm, optimum ZnO thickness of 10 nm, optimum working temperature of 300 K and optimum energy band gap of 1.5 eV. The best device performance consisting of these optimum values results in a PCE of 30.51% correlated to FF of 83.7%, JSC of 47.188 mA.cm-2 and VOC of 0.773 Volt. The results are promising and pave the way towards high PCE of CISSe-based solar. However, there might be a differences when these factors are applied in an experimental procedure due to the preparation conditions.